2017
DOI: 10.17511/jopm.2017.i01.08
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological spectrum of cervical biopsies – a 5 year retrospective study

Abstract: Introduction: cervix is a gateway to numerous non neoplastic and neoplastic gynecological lesions. Cervical cancer is the leading cancer in Indian women and second most common cancer in women worldwide next to breast cancer. Objectives: 1) To study the histopathological features of cervical lesions. 2) To study the age distribution and relative frequency of various cervical lesions. Materials and Methods: This is 5 years retrospective study of all cervical biopsies received from 2011-2015 in the department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The cervix is vulnerable to many pathological changes such as non-neoplastic and neoplastic lesions. (1,2). The nonneoplastic cervical lesions are distributed across all age groups, more commonly in sexually active women.…”
Section: Introductionmentioning
confidence: 99%
“…The cervix is vulnerable to many pathological changes such as non-neoplastic and neoplastic lesions. (1,2). The nonneoplastic cervical lesions are distributed across all age groups, more commonly in sexually active women.…”
Section: Introductionmentioning
confidence: 99%
“…Cervicitis, in the index study, was the most common non-neoplastic lesion with most cases occurring in the fourth decade of life. Kumari et al also observed that cervicitis was the most common nonneoplastic lesion with majority of cases identified within 30-41 years of age [64]. Craig and Lowe, 2003, revealed a similar result with rarity of the lesion in females below twenty years in contrast to the report presented by Omoniyi-Esan et al, whose findings showed that 10% of cervicitis was observed in adolescence [65,66].…”
Section: Discussionmentioning
confidence: 88%
“…In recent years, it has become clear that HPV plays a critical role in the pathogenesis of nearly all cervical squamous cell carcinomas [9]. In the study, lesions were classified as non-neoplastic, premalignant, or malignant, as in previous studies [7,8,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%